(untitled) (CAHIERS MAGELLANES-NS, 2024)
Quail raising has gained popularity in Iraq, particularly in Kurdistan, during the past decade due to high demand for meat and eggs. This study examined how three different plumage colours of native quails in Kurdistan, Iraq, affect their performance and certain carcass features. 432 one-day-old quail chicks were divided into three groups based on plumage colour: White (WPC), Black (BPC), and Brown (BrPC). Each group was observed for 42 days. Various characteristics such as live body weight (LBW), weight growth (WG), feed intake (FI), feed conversion ratio (FCR), mortality (M%), and carcass weight (liver and heart) were measured for males and females at various ages. Results showed that the LBW of WPC quails was significantly greater than BPC quails at hatch. However, at 42 days, BrPC quails had significantly higher LBW, WG, FI, and superior FCR compared to WPC quails. Furthermore, female subjects exhibited significantly(p<0.05) higher body weight, carcass weight, and heart weight at 28 and 42 days of life (P<0.05). The interaction effect revealed that female birds of the BrPC line had significantly higher LBW and WG compared to other plumage colour lines (P0.05). Male WPC had considerably higher carcass weight compared to females (P<0.05). Females from the WPC line exhibited significantly lower ovary weight compared to the other two lines (P0.05). In conclusion, the data showed variations in weight characteristics among different lineages in comparison to previous research.